Left hepatic lobe herniation through an incisional anterior abdominal wall hernia and right adrenal myelolipoma: a case report and review of the literature - Nuño-Guzmán, Carlos M (BioMed Central, 2012)
INTRODUCTION: Herniation of the liver through an anterior abdominal wall hernia defect is rare. To the best of our knowledge, only three cases have been described in the literature. CASE PRESENTATION: A 70-year-old Mexican woman presented with a one-week history of right upper quadrant abdominal pain, nausea, vomiting, and jaundice to our Department of General Surgery. Her medical history included an open cholecystectomy from 20 years earlier and excessive weight. She presented with jaundice, abdominal distension with a midline surgical scar, right upper quadrant tenderness, and a large midline abdominal wall defect with dullness upon percussion and protrusion of a large, tender, and firm mass. The results of laboratory tests were suggestive of cholestasis. Ultrasound revealed choledocholithiasis. A computed tomography scan showed a protrusion of the left hepatic lobe through the anterior abdominal wall defect and a well-defined, soft tissue density lesion in the right adrenal topography. An endoscopic common bile duct stone extraction was unsuccessful. During surgery, the right adrenal tumor was resected first. The hernia was approached through a median supraumbilical incision; the totality of the left lobe was protruding through the abdominal wall defect, and once the lobe was reduced to its normal position, a common bile duct surgical exploration with multiple stone extraction was performed. Finally, the abdominal wall was reconstructed. Histopathology revealed an adrenal myelolipoma. Six months after the operation, our patient remains in good health. CONCLUSIONS: The case of liver herniation through an incisional anterior abdominal wall hernia in this report represents, to the best of our knowledge, the fourth such case reported in the literature. The rarity of this medical entity makes it almost impossible to specifically describe predisposing risk factors for liver herniation. Obesity, the right adrenal myelolipoma mass effect, and the previous abdominal surgery are likely to have contributed to incisional hernia formation.